Professional Identities in Initial Teacher Education The Narratives and Questions of Teacher Agency - Mifsud, Denise (Springer International Publishing, 2018)
This book explores the perception, construction and performance of professional identities in initial teacher education (ITE). Drawn from a collection of narrative data from postgraduate students, the author explores these topics through school placement, career choice motivations, the attractiveness of the teaching profession, the presentation of personal and professional selves, and professional standards. The findings of this study can be applied across both European and global dimensions. The use of narrative methodology for data collection, in addition to the implementation of various theoretical frameworks, ensures that the book holds a wide appeal. Interweaving theory with personal experiences, this reflective book will appeal to students and scholars of ITE, as well as early career researchers and practitioners.